Human and Social Capital as Antecedents of Spiritual Capital on MSME Innovation - Bima Cinintya Pratama; Amrizah Kamaluddin; Azmi Fitriati; Shukriah Saad; Maulida Nurul Innayah; Siti Syaqilah Hambali (Faculty of Economic and Business, 2024)
Research Originality: The originality of this paper lies in its inclusion of the mediating role of human capital and social capital in the connection between spiritual capital and MSME innovation capability.Research Objectives: This study examined how Innovation in MSMEs by using antecedents of their spiritual capital, human capital, and social capital.Research Methods: This study using sample from MSME operators and owners located in the western part of Central Java Province. The analysis conducted in this study was using Structural Equation Model.Empirical Results: The results found that spiritual capital, human capital, and social capital has a significant positive effect on innovation capability. In addition, human capital and social capital can mediate the relationship between spiritual capital and innovation capability.Implications: From the results of this study, it can be implied that spiritual capital, human capital, and social capital is very important for MSMEs managers and owners to create innovation to make value-added for their business. Therefore, MSMEs should concern on the management of those capitals.JEL Classification: E31, F31, C22How to Cite:Pratama, B. C., Kamaluddin, A., Fitriati, A., Saad, S., Innayah, M. N., & Hambali, S. S. (2024). Human and Social Capital as Antecedents of Spiritual Capital on MSME Innovation. Etikonomi, 23(2), 238 – 396. https://doi.org/10.15408/etk.v23i2.32201.